Esg ratings divergence & developing a proprietary Esg scorecard - Bonnike, Lucas Sander (2020)
This paper analyses the divergence in Environmental, Social, and Governance(ESG) ratings between two leading providers: Sustainalytics and RobecoSAM.It finds that there are significant divergences in ratings between the two providers and that the rating correlation between them is much lower when compared to the correlation observed between credit rating agency scores. This applies to both their composite ESG ratings and their unidimensional Environmental, Social, and Governance scores. Additionally, this paper attempts to build a transparent, reliable, and cost-effective proprietary ESG scorecard by using a limited amount of data points, however the resulting scores are weakly correlated to the agency ratings.